In Rural Areas, Buprenorphine Waiver Adoption Since 2017 Driven by Nurse Practitioners And Physician Assistants - Barnett, Michael L. (Health Aff (Millwood), 2019)
Few patients with opioid use disorder receive medication for addiction treatment. In 2017, the Comprehensive Addiction and Recovery Act enabled nurse practitioners (NPs) and physician assistants (PAs) to obtain federal waivers that allowed them to prescribe buprenorphine, a key medication for opioid use disorder. The waiver expansion was intended to increase patient access to opioid use treatment, which was particularly important for rural areas with few physicians. However, little is known about adoption of these waivers by NPs or PAs in rural areas. Using federal data, we examined waiver adoption in rural areas and its association with scope of practice regulations, which set the extent to which NPs or PAs can prescribe medication. From 2016 to 2019, the number of waivered clinicians per 100,000 population in rural areas increased by 111 percent. NPs and PAs accounted for more than half of this increase and were the first waivered clinicians in 285 rural counties with 5.7 million residents. In rural areas, broad scope of practice regulations were associated with twice as many waivered NPs per 100,000 population as restricted scopes of practice were. The rapid growth in the numbers of NPs and PAs with buprenorphine waivers is a promising development in improving access to addiction treatment in rural areas.